The Role of the Padang Panjang Vocational Training Center in Creating Jobs - Zuryani, Fitri; Iswadi, Iswadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this thesis is the role of the Padang Panjang Job Training Center in creating job opportunities (study of community empowerment in education). The purpose of this discussion is to find out the program of the Training Department at the Padang Panjang Job Training Center (BLK), as well as the obstacles or constraints experienced by the Padang Panjang BLK in implementing the program and to know the impact of the Padang Panjang BLK. The type of research used is field research (field research), with qualitative methods, descriptive approach. Sources of data used are primary data sources, data directly found in the field from the first informant and secondary data sources, namely data obtained indirectly by researchers at the research location such as books, journals, and other scientific works. Data collection techniques that researchers use through observation, interviews, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion drawing. To check the validity of the data, the researchers used source triangulation, technique triangulation, and time triangulation. BLK Padang Panjang as an institution received less feedback from participants regarding their existence. BLK Padang Panjang has had a great impact on participants by increasing their skills and expertise. The impact of the Padang Panjang BLK on the community reduces unemployment in Padang Panjang and its surroundings, because many young people find work both at home and abroad.